Effect of Microstructural Anisotropy on Fracture Toughness of Selective‐Laser‐Melted 15‐5 PH Stainless Steel. Issue 3 (3rd February 2023) - He, Ke; Lv, Binghua; Niu, Xiaodong; Mao, Zhongfa; Zhang, Lujie; Rao, Heng; Cao, Sheng
Abstract : Herein, the influence of microstructure anisotropy on fracture toughness of selective laser melting‐fabricated and directly aged 15‐5 PH stainless steel is investigated. A bimodal columnar (within the melt pool) and equiaxed (at the melt pool boundary) microstructure forms on the vertical plane, which results in a higher yield strength in the horizontal direction than the vertical direction. For fracture toughness, the K IC value is 10% higher in the specimen with the crack propagation perpendicular to the build direction than parallel to the build direction. The main cause for such an anisotropic fracture toughness is related to the circuitous crack path along the melt pool boundary when the crack propagation is perpendicular to the build direction. Abstract : Selective laser melting‐fabricated 15‐5 PH SS specimens contain a fine equiaxed microstructure on the horizontal plane and a bimodal columnar and equiaxed microstructure on the vertical plane. Such an anisotropic microstructure leads to different fracture toughnesses in horizontal and vertical orientations.